2013
DOI: 10.3109/21678421.2013.764568
|View full text |Cite
|
Sign up to set email alerts
|

Randomized double-blind placebo-controlled trial of acetyl-L-carnitine for ALS

Abstract: Our objective was to assess the effects of acetyl-L-carnitine (ALC) with riluzole on disability and mortality of amyotrophic lateral sclerosis (ALS). Definite/probable ALS patients, 40-70 years of age, duration 6-24 months, self-sufficient (i.e. able to swallow, cut food/handle utensils, and walk), and with forced vital capacity (FVC) > 80% entered a pilot double-blind, placebo-controlled, parallel group trial and were followed for 48 weeks. ALC or placebo 3 g/day was added to riluzole 100 mg/day. Primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 27 publications
0
62
1
Order By: Relevance
“…For example, in one of the lithium trials,19 the composite outcome of severe loss of autonomy, defined as the time from inclusion to death/tracheotomy or at least two of three selected ALSFRS-R scores (ie, ≤1 for swallowing, ≤1 for walking, or ≤2 for respiratory insufficiency), was able to capture a percentage of events around 15% at 6 months and above 30% at 12 months. Similarly, in the acetyl- l -carnitine trial,4 the composite primary outcome of loss of self-sufficiency, defined as inability to swallow, cut food/handle utensils and walk, was observed in more than 80% of patients at 12 months.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, in one of the lithium trials,19 the composite outcome of severe loss of autonomy, defined as the time from inclusion to death/tracheotomy or at least two of three selected ALSFRS-R scores (ie, ≤1 for swallowing, ≤1 for walking, or ≤2 for respiratory insufficiency), was able to capture a percentage of events around 15% at 6 months and above 30% at 12 months. Similarly, in the acetyl- l -carnitine trial,4 the composite primary outcome of loss of self-sufficiency, defined as inability to swallow, cut food/handle utensils and walk, was observed in more than 80% of patients at 12 months.…”
Section: Discussionmentioning
confidence: 92%
“…Combined outcome measures including survival, tracheotomy, NIV and/or selected domains of the ALSFRS-R scale showed better performances compared to survival or mean ALSFRS-R decline alone in several studies 4 5 12 17 19 20. For example, in one of the lithium trials,19 the composite outcome of severe loss of autonomy, defined as the time from inclusion to death/tracheotomy or at least two of three selected ALSFRS-R scores (ie, ≤1 for swallowing, ≤1 for walking, or ≤2 for respiratory insufficiency), was able to capture a percentage of events around 15% at 6 months and above 30% at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent suggestions that modifications of the epigenome might be of interest for understanding clinical variability in ALS [19, 35] might further justify the attempts of testing in the future other compounds able to modify histone acetylation or histone and/or DNA methylation [36]. In fact, in spite of the fact that ALS clinical heterogeneity might imply differences in the involved pathophysiology, a common downstream pathway converging on the regulation of mRNA expression has been repeatedly demonstrated since the discovery of TARDP43 and FUS/TLS mutations in ALS [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…A small (n=42 treated, 40 placebo) randomized double-blind placebo-controlled pilot study of acetyl-L-carnitine, showed an increase in median survival and slower ALSFRS-R and FVC decline in the patients taking L-carnitine 3g/day. No significant side effects were reported and the authors concluded that a phase III trial is needed to confirm these preliminary findings (60). …”
Section: Types Of Cam That Pals Commonly Ask Aboutmentioning
confidence: 96%